An Historical Geography of Iran. - Barthold, Vasilii Vladimirovich.
1 online resource (309 pages)
Keywords: This volume is a compendium of the rich archeological and literary evidence on the Iranian world in its larger sense, comprising part of what is now Soviet Central Asia and Afghanistan as well as Iran proper. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.